The Brazil-Argentina gemini group for the study of globular cluster systems (BAGGs GCs): Flamingos-2 and GMOS data for NGC 1395 - Faifer, Favio Raúl (2017)
In this letter, we present preliminary results of the analysis of Flamingos-2 and GMOS-S photometry of the globular cluster (GC) system of the elliptical galaxy NGC1395. This is the first step of a long-term Brazilian-Argentinian collaboration for the study of GC systems in early-type galaxies. In the context of this collaboration, we obtained deep NIR photometric data in two different bands (J and Ks), which were later combined with high quality optical Gemini + GMOS photometry previously obtained by the Argentinian team. This allowed us to obtain different color indices, less sensitive to the effect of horizontal branch (HB) stars for several hundreds of GC candidates, and to make an initial assessment of the presence or absence of multiple GC populations in colors in NGC1395.